Role of viral antigens in destructive cellular immune responses to adenovirus vector-transduced cells in mouse lungs. - Yang, Y (1996)
Adenoviruses missing E1 have been used as gene delivery vectors to the lungs for the treatment of cystic fibrosis. Transient expression of the recombinant gene and the development of inflammation have been two major limitations to the application of first-generation recombinant adenoviruses for gene therapy. Studies with mouse models of liver- and lung-directed gene therapy suggested that CD8+ cytotoxic T lymphocytes (CTLs) are effectors that contribute to extinction of transgene expression. The precise antigens responsible for activation of CTLs have not been identified. In this study, we examine the relative contributions of viral proteins versus the transgene product to the activation of CTLs which eliminate transgene-containing cells in mouse lungs. Instillation of a lacZ-expressing virus into the lungs of C57BL/6 mice elicited CTL responses to both viral proteins and the transgene product, beta-galactosidase, which collectively contribute to loss of trans-gene expression in mouse airways. Similar results were obtained in two experimental models in which the animals should be tolerant to the transgene, i.e., lacZ virus delivered to an animal transgenic for lacZ and a virus expressing the liver-specific enzyme ornithine transcarbamylase administered to the lungs of various strains of immune-competent mice. These data confirm the hypothesis that CTLs specific for viral antigens contribute to the problem of transgene instability in mouse lungs and indicate that CTLs specific for transgene product alone cannot account for the observed problem.